Comparision of Properitoneal Non Tension Sutured Mesh Repair Versus Conventional Mesh Repair for Reducing Postoperative Pain in Direct Inguinal Hernia - A Randomised Control Trial - Sangolli. M.S2, Gogate A.S2, Sindhuri. G, Hiremath. M.B, Ajay kumar. G1,2*, (Recent Research in Science and Technology, 2010)
Abstract Background: Numerous repairs exist for direct inguinal hernias. These repairs are limited by the shortcomings of their respective technique. Each study has its own self limitations for the reduction of postoperative pain. With the introduction of Properitoneal nontension sutured mesh repair, the postoperative pain has been lessened,proving efficacy in terms of decreased hospital stay, patient comfort and early return to activities. Hence there is need for comparing Properitoneal nontension sutured mesh repair with Conventional mesh repairs for the reduction of postoperative pain. Materials and Methods: A Randomized clinical trial was designed with a sample size of 60 patients, which were divided into 2 groups; Group A (properitoneal non tension sutured mesh repair) & Group B (conventional mesh repair). These two groups were analyzed for postoperative pain (visual analogue score) from 2 weeks to 12 weeks. Results: On analysis, three months follow up pain score is significantly less in the group A patients at 2week and even upto 8weeks, thereafter no patients experienced any pain. In group B the pain is significantly more than Group A and minimal pain persisted until 11weeks. Conclusion: The results of the new technique demonstrate that it provides less postoperative pain than has been reported in other nontension mesh repairs. There is apparent advantage in the use of properitoneal nontension sutured mesh repair compared to conventional mesh repair. Short term follow up of the study did not allow any conclusion regarding recurrence rates, thus larger cohorts with longer follow up are needed. Keywords: hernia repair, properitoneal nontension sutured mesh repair, lichenstein mesh repair <span style="line-height: 110%; font-family: ";Arial Narrow";,";sans-serif";; color: black; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">